Depiction of lord Vayu on the northern wall of the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
On the opposite end of the northern wall of the garbhagriha (sanctum sanctorum), there is a representation of Vayu (one of the deities of the cardinal directions). Although the head and arms of the figure are damaged, he is identifiable from the remaining parts of the image. Vayu, portrayed as a beautiful and youthful figure, is depicted holding a staff with a banner in his upper right hand. The banner extends behind his head. His lower right hand is in the varada hasta (boon-giving) gesture, holding akshamala (rosary). At the bottom, an antelope is depicted.